2022
DOI: 10.1002/humu.24345
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and follow‐up of glycogen storage disease (GSD) type VI from the largest GSD center in China

Abstract: Glycogen storage disease (GSD) Type VI is a glycogenolysis disorder caused by variants of PYGL. Knowledge about this disease is limited because only approximately 50 cases have been reported. We investigated the clinical profiles, molecular diagnosis, and treatment outcomes in patients with GSD VI from 2000 to 2021. The main initial clinical features of this cohort include hepatomegaly, short stature, elevated liver transaminases, hypertriglyceridemia, fasting hypoglycemia, and hyperuricemia. After uncooked co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 28 publications
0
9
1
Order By: Relevance
“…The most important symptom in this study was a distended abdomen with hepatomegaly, similar to several other studies. [ 11 , 13 , 14 ] However, many studies reported patients with short stature versus none in our study. [ 11 , 13 , 15 ] Case 2 showed developmental delay and was eventually diagnosed with autism.…”
Section: Discussioncontrasting
confidence: 53%
See 4 more Smart Citations
“…The most important symptom in this study was a distended abdomen with hepatomegaly, similar to several other studies. [ 11 , 13 , 14 ] However, many studies reported patients with short stature versus none in our study. [ 11 , 13 , 15 ] Case 2 showed developmental delay and was eventually diagnosed with autism.…”
Section: Discussioncontrasting
confidence: 53%
“…[ 11 , 13 , 14 ] However, many studies reported patients with short stature versus none in our study. [ 11 , 13 , 15 ] Case 2 showed developmental delay and was eventually diagnosed with autism. Other studies reported developmental delay or muscle hypotonia in patients with GSD VI[ 16 , 17 ] and autism in patients with GSD II,[ 18 ] but no studies have reported autism in patients with GSD VI.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations